Blood Women in Perspective of Fiqh Syafi’iyyah and Medical Science - Abdullah; Mustafa Kamal; Siti Zalikha; Sadiqul Wahdi; Muhammad Ikbal (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2019)
Changes in the menstrual period (menstrual cycle) because of changes in the cycle have an impact on the legal status of blood that comes out. According to Syafi'iyyah Fiqh when blood comes out for a longer time due to excessive bleeding caused by contraception it will become khiyar between menstrual blood or istihadhah blood, whereas in medical science there is no term istihadhah for women, only menstrual blood and puerperal blood. Researchers try to raise this issue as material that deserves to be studied in depth, with the title "Blood Women in Perspective of Fiqh Syafi’iyyah and Medical Science". The results showed that in Syafi'iyyah Fiqh there were several types of blood that came out of one of the female reproductive organs (womb), menstrual blood, puerperal blood, and istihadhah blood. While in medical science there were only 2 known types of women's blood, namely: menstrual blood (menstruation) and puerperium blood (puerperal).